SPECIES IDENTIFICATION AND DIFFERENTIATION OF DERMATOPHYTES, ANTIFUNGAL SUSCEPTIBILITY PROFILE FROM A TERTIARY CARE CENTRE IN CENTRAL INDIA - Sakshi Vishnoi; Madhurendra Singh Rajput (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective:   One of the oldest disease, dermatophytosis, is growing more common in the modern era. Because of this, understanding antifungal susceptibility has become crucial in the modern era..Material and Methods: This 18-month prospective study included all dermatophytes that were isolated during that time. Dermatophytes were discovered using standard phenotypic techniques. As per the Clinical Laboratory Standard Institute M38A2, antifungal susceptibility testing was carried out for griseofulvin, terbinafine, and itraconazole, and minimum inhibitory concentrations (MICs) were determined within 5 days.Results: Information on the patient and related risk factors were noted. Of the 320 patients with dermatophytosis of the skin, 79.3% had fixed dose combination medications with steroids. 303 of the 272 dermatophytes that were isolated throughout the study period came from skin scrapings, and 48 came from nail samples. Presentations of tinea corporis with cruris were the most frequent. Trichophyton mentagrophytes complex (40.3%)was the most often isolated dermatophyte from skin scrapings (129 out of 272), whereas Trichophyton rubrum complex ( 66%) ,( 32 out of 48 ) was recovered from nail samples. Itraconazole had the lowest MICs, followed by terbinafine and griseofulvin, according to the MIC50 and MIC90 data. In summary Antifungal resistance and species distribution epidemiology are evolving, necessitating ongoing monitoring of these dermatophyte characteristics.